Investigation on suitability of pulse duration parameter for HeLa cells line proliferation properties towards anti-cancer application - Azizulkarim, Azra Hazwanie; Abdul Jamil, Muhammad Mahadi; Adon, Mohamad Nazib; Ahmad, Muhammad Shukri; Mohamad Sharif, Johan; Ngadi, Md Asri; Ambar, Radzi (IOP Publishing, 2018)
In order to bring up a cells or tissue with a gene or DNA, Electroporation parameter such as pulse duration, field strength and number of pulse plays the most important aspect. Thus, the aim of this paper is to optimize the pulse duration parameter for HeLa cells line. This is very important because nowadays, research on EP factors is still in limited mode. Moreover, suitable and applicable pulse duration parameter would ensure successful treatment with least possible side effect. In this paper, HeLa cells or known as cervical cancer cells was used to induce into a single pulse electric field. Therefore, to achieve the aim of this study, field strength of 500V/cm was preferred and the pulse duration was varied in the range of 100μs, 500μs, 1ms, 2ms and 5ms to obtain lowest proliferation rate and inhibit growth of HeLa cells. The result obtained shows that HeLa cell induced to 500V/cm with pulse duration of 100μs, induced the lowest proliferation rate (45%) as compared to initial reading density (control) after 48 hours of culture. Thus, further research based on this work may pave the way for an anti-cancer application through the study of the effect of pulse duration parameter on HeLa cells.